STUDI POTENSI BIOMASSA HUTAN SAGU (Metroxylon Sp) DI DESA TULEHU KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Haduaci, Doni; Mardiatmoko, Gun; Pattimahu, Debby (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Sago forests (Metroxylon sp) in Tulehu Village, Salahutu District, Central Maluku Regency are one of the staple food sources of the Maluku community that have been consumed for generations. Various parts of sago from leaf stalks to trunks have been widely studied. However, research related to sago biomass has not been done much. In this regard, this paper aims to determine the potential biomass and carbon reserves stored in sago forests in Tulehu Village for the purposes of handling climate change. The biomass and carbon content reserves to be determined are sago at the pole and tree levels. The method used was 3 survey routes with 30 measurement plots using purposive sampling, observation, then analysis and estimation of biomass and stored carbon reserves. The calculation results at the pole level of sago obtained a biomass of 27 tons/ha and stored carbon reserves of 14 tons/ha. At the tree level of sago, a biomass of 42 tons/ha and stored carbon reserves of 20 tons/ha were obtained.